2015
DOI: 10.1016/j.scitotenv.2014.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic and hydrogeochemical characterization of high-altitude karst aquifers in complex geological settings. The Ordesa and Monte Perdido National Park (Northern Spain) case study

Abstract: The Ordesa and Monte Perdido National Park, located in the Southern Pyrenees, constitutes the highest karst system in Western Europe. No previous studies regarding its geochemical and isotopic groundwater characterization are available in this area. This work presents the results of field and sampling campaigns carried out between July 2007 and September 2013. The groundwater presents high calcium bicarbonate contents due to the occurrence of upper Cretaceous and lower Paleocene--Eocene carbonate materials in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
44
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 42 publications
(37 reference statements)
12
44
0
9
Order By: Relevance
“…(10 2 –10 3 cells/mg dust) and relatively higher median concentrations for Enterobacteriaceae (10 3 cells/cm 2 dust) and Bifidobacteriacae spp. (10 4 cells/mg dust) (Kaarakainen et al, 2009; Rinatala and Nevalainen, 2006; Scherer et al, 2014; Valknonen et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(10 2 –10 3 cells/mg dust) and relatively higher median concentrations for Enterobacteriaceae (10 3 cells/cm 2 dust) and Bifidobacteriacae spp. (10 4 cells/mg dust) (Kaarakainen et al, 2009; Rinatala and Nevalainen, 2006; Scherer et al, 2014; Valknonen et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In prior studies, microbial DNA-based methods using quantitative PCR (qPCR) methods have demonstrated good reliability and applicability to large cohorts for assessment of microbial exposures in home dust samples (Fujimura et al, 2012; Kaarakainen et al, 2009; Rintala et al., 2008; Scherer et al, 2014). DNA-based methods may provide a less biased estimate of microbial exposures than culture-based methods, which require organism viability and cultivability (Kaarakainen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies around the world have reported on the effect of isotopic lapse rates of precipitation in streamwater (Jeelani, Saravana Kumar, & Kumar, ; Wen et al, ), groundwater (Lambán et al, ; O'Driscoll, DeWalle, McGuire, & Gburek, ), and soil water (O'Driscoll et al, ). However, this effect can be masked by other fractionating processes as well as elevation‐dependent recharge processes.…”
Section: Background Of Isotope Hydrologymentioning
confidence: 99%
“…A detailed isotopic analysis of groundwater discharging from Ash Meadows, Nevada, confirmed this interpretation, claiming flow to have come from the opposite direction, and proposed that structurally complex basins are not as interconnected as previously thought (Bushman et al 2010). Similar studies from the Ordesa Na Monte Perdido National Park in Northern Spain determined control of elevation of precipitation on the isotopic composition of recharge and discharge zones (Lamban et al 2015).…”
Section: Introductionmentioning
confidence: 77%